2014
DOI: 10.3109/17453674.2014.931194
|View full text |Cite
|
Sign up to set email alerts
|

No clinical benefit of gender-specific total knee arthroplasty

Abstract: Background and purposeThere is no consensus regarding the clinical relevance of gender-specific prostheses in total knee arthroplasty (TKA). We summarize the current best evidence in a comparison of clinical and radiographic outcomes between gender-specific prostheses and standard unisex prostheses in female patients.MethodsWe used the PubMed, Embase, Cochrane, Science Citation Index, and Scopus databases. We included randomized controlled trials published up to January 2013 that compared gender-specific prosthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…This serves as a cautionary example that not all changes to implants driven by morphologic findings result in discernible improvements. We note, though, that the ML width of the distal femur is associated primarily with femur length, not gender [37], which could play a role in the inability of gender-specific implants to confer a clinical benefit [4]. The differences in aspect ratio and femoral shape identified between ethnicities in our analysis may prove to be a more relevant factor in the long-term success of TKA, and is worthy of additional analysis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This serves as a cautionary example that not all changes to implants driven by morphologic findings result in discernible improvements. We note, though, that the ML width of the distal femur is associated primarily with femur length, not gender [37], which could play a role in the inability of gender-specific implants to confer a clinical benefit [4]. The differences in aspect ratio and femoral shape identified between ethnicities in our analysis may prove to be a more relevant factor in the long-term success of TKA, and is worthy of additional analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Although individual studies have been conducted measuring relevant morphologic endpoints among various distinct populations [1, 2, 4, 6, 8, 13, 14, 23, 24, 26, 27, 29–32, 34, 36, 39, 4143, 45–47, 5054, 56], to our knowledge to date there has not been a systematic analysis of their findings to clarify what specific differences exist among ethnicities. We hoped that performing this analysis would facilitate research in the clinical implications of these anatomic differences and determine whether design initiatives would be merited to address the potential for compromised implant fit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in female patients by Zaki et al [31], early clinical outcomes for knees with a gender-specific prosthesis were found to be similar to knees with a standard prosthesis there by showing no advantage of gender-specific knee prosthesis over standard unisex knee prosthesis with regards to early clinical outcomes. Genderspecific prosthesis didn't appear to confer any advantage in terms of clinician as well as patient-reported outcomes in study by Cheng et al [32] for the female knee. In present study of 1,635 high flex knees, an aggregate of 8 (0.49%) amendments were done, including four (0.24%) for infection, three (0.18%) for aseptic loosening, and one (0.06%) for dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Sir –We thank Dr. Xie and his colleagues for their great interest in performing such an in-depth methodological assessment of our article ( Cheng et al 2014 ). We would like to answer their questions that were raised in their letter to the editor.…”
mentioning
confidence: 99%